2022
DOI: 10.3389/fnhum.2022.921490
|View full text |Cite
|
Sign up to set email alerts
|

Neural Plasticity in Spinal and Corticospinal Pathways Induced by Balance Training in Neurologically Intact Adults: A Systematic Review

Abstract: Balance training, defined here as training of postural equilibrium, improves postural control and reduces the rate of falls especially in older adults. This systematic review aimed to determine the neuroplasticity induced by such training in younger (18–30 years old) and older adults (≥65 years old). We focused on spinal and corticospinal pathways, as studied with electrophysiology, in people without neurological or other systemic disorders. We were specifically interested in the change in the excitability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Previous studies have shown decreasing soleus H-re ex amplitude when human body balance is challenged (i.e., from lying to standing(Mynark & Koceja, 2002), or from standing to walking(Capaday & Stein, 1986)). In our study, reduced COP indicated that balance control ability has been improved after balance re ex consistently decreases in younger people, while it is less affected or increases in older people after balance training, even the timing of H-re ex measurement is different in these studies(Sun et al, 2022). Therefore, mechanisms of balance training-induced corticospinal adaptation seem not fully resolved, and contradictory results of those studies may be related to differences in the duration of training, balance tasks, and the age of the participants.…”
mentioning
confidence: 47%
“…Previous studies have shown decreasing soleus H-re ex amplitude when human body balance is challenged (i.e., from lying to standing(Mynark & Koceja, 2002), or from standing to walking(Capaday & Stein, 1986)). In our study, reduced COP indicated that balance control ability has been improved after balance re ex consistently decreases in younger people, while it is less affected or increases in older people after balance training, even the timing of H-re ex measurement is different in these studies(Sun et al, 2022). Therefore, mechanisms of balance training-induced corticospinal adaptation seem not fully resolved, and contradictory results of those studies may be related to differences in the duration of training, balance tasks, and the age of the participants.…”
mentioning
confidence: 47%